Cambodia : Technical Assistance Report-Tax Administration Modernization Priorities 2019-23. (IMF Staff Country Reports; Country Report, 2018)
This FAD mission reviewed recent progress to improve tax administration and identified areas of priority tax administration modernization for 2019-23. The MEF has been implementing the RMS, a major component of which is the strengthening of the administration of the GDT. As the RMS ends in 2018, the MEF is now developing the next phase of reforms to strengthen the revenue system of Cambodia over the period 2019 to 2023. The GDT has made significant progress with implementing the RMS measures under its responsibility, and achieved extremely positive revenue growth and collections. The GDT has completed 71 out of the 86 RMS tax administration measures; the remaining 15 are under active progress. Since 2012, the GDT has routinely exceeded its revenue targets, and year-on-year revenue growth has far exceeded the annual levels of economic growth. Cambodia's 2017 tax-to-GDP ratio of 17.2 percent is now comparable with many regional countries.